Social and educational characteristics of the health status of pupils - sportsmen - S.V. Shmalyey; T.I. Scherbina (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to analyze the biomedical and social determinants of health and hygiene of pupils athletes. Material: the study involved 60 athletes 12-15 years and their peers (n = 60), which are not involved in sports, as well as parents of schoolchildren. Comprehensive study was conducted using questionnaires by the "copy - a couple." Results: it was found that young athletes have less influence adverse biological factors than their peers. Systematic sports distract students from passive pastime and regulate rational mode of the day. Food of young athletes has the following features: Custom mode, high multiplicity meal predominance in the diet of vegetables, meat and dairy products. Found that most of the families of pupils athletes have sufficient material level and adequate housing. At the same time, parents of the ordinary students are more prone to the spread of harmful habits. Psychological climate in families of pupils is low conflict. Medical support is stable, but not sufficient. More than half of the families of pupils - athletes perform medical advice given extra hygiene knowledge. Conclusions: the students who participate in sports is a specific social-demographic group. The main factor of social and pedagogical state of the family is the attitude of the parents to the child's health.